2004
DOI: 10.1177/1523422304263327
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Self-Directed Learning and Its Implications for Human Resource Development

Abstract: The problem and the solution. Learners are increasingly being challenged to assume more responsibility for their own learning and development in work organizations. Although the concept of self-directed learning (SDL) has a rich history of research and practice in the adult education field, it has not received considerable attention in the context of HRD. Therefore, this article will introduce SDL and overview its various conceptualizations, examine approaches and techniques that can be used in HRD practice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(171 citation statements)
references
References 44 publications
5
161
0
5
Order By: Relevance
“…Our findings are in line with the notions expressed by Ellinger (2004) who states that the idea of the learner as a self-directed learner who oversees different options and carefully plans and monitors his own learning trajectory and career is perhaps more an ideology than an empirical proven fact (Van der Klink et al, 2007).…”
Section: Conclusion and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings are in line with the notions expressed by Ellinger (2004) who states that the idea of the learner as a self-directed learner who oversees different options and carefully plans and monitors his own learning trajectory and career is perhaps more an ideology than an empirical proven fact (Van der Klink et al, 2007).…”
Section: Conclusion and Discussionsupporting
confidence: 77%
“…Based on interviews with 78 learners, Spear and Mocker (1984) demonstrated that conscious and deliberate planning of learning activities is even quite rare. As Ellinger (2004) concluded in her review, learners more often respond to circumstances and events rather than planning carefully in advance their courses of actions. Many informal learning experiences occur as a side-effect of some other activity and it even occurs although employees are not always conscious of it and they do not intentionally seek for learning experiences.…”
Section: Factors Influencing Informal Learningmentioning
confidence: 99%
“…This means that it may be difficult to use self-directed and computer-mediated learning modules with the MSCEIT. Thus, HRD practitioners who emphasize self-directed learning (SDL), which calls on employees to assume greater responsibility for their own learning and development, may find that use of the MSCEIT may not yield large positive effects (Ellinger, 2004).…”
Section: Emotional Intelligence Measuresmentioning
confidence: 99%
“…This means that it may be difficult to use self-directed and computer-mediated learning modules with the MSCEIT. Thus, HRD practitioners who emphasize self-directed learning (SDL), which calls on employees to assume greater responsibility for their own learning and development, may find that use of the MSCEIT may not yield large positive effects (Ellinger, 2004).Although using the MSCEIT has several drawbacks, it readily lends itself to a comprehensive yet manageable set of developmental activities and also offers advantages for HRD research. The focus is on specific abilities as HUMAN RESOURCE DEVELOPMENT QUARTERLY • DOI: 10.1002/hrdq opposed to constellations of personality or behavioral competencies (as in the ECI-2, EQ-i, and EIQ) that are, by definition, less amenable to change through HRD applications.…”
mentioning
confidence: 99%
“…In self-development, the employee is ultimately responsible for determining the levels of these attributes, as he/she selects the self-development activity in which to participate (Confessore, 1992;Ellinger, 2004). There is no guarantee that the employee will make appropriate choices with respect to participation in self-development activities that contain optimal levels of the instructional design attributes.…”
Section: Recommendations For Army Leadersmentioning
confidence: 99%